Development of microvalves for gas flow control in micronozzles using PVDF piezoelectric polymer - Wiederkehr, R. S.; Salvadori, M. C.; Degasperi, F. T.; Cattani, M. (IOP Publishing, 2008)
This work describes a fabrication and test sequence of microvalves installed on micronozzles. The technique used to fabricate the micronozzles was powder blasting. The microvalves are actuators made from PVDF (polivinylidene fluoride), that is a piezoelectric polymer. The micronozzles have convergent-divergent shape with external diameter of 1mm and throat around 230μm. The polymer have low piezoelectric coefficient, for this reason a bimorph structure with dimensions of 2mm width and 4mm of length was build (two piezoelectric sheets were glued together with opposite polarization). Both sheets are recovered with a conductor thin film used as electrodes. Applying a voltage between the electrodes one sheet expands while the other contracts and this generate a vertical movement to the entire actuator. Appling +300V DC between the electrodes the volume flux rate, for a pressure ratio of 0.5, was 0.36 sccm. Applying -200V DC between the electrodes (that means it closed) the volume flux rate was 0.32 sccm, defining a possible range of flow between 0.32 and 0.36 sccm. The third measurement was performed using AC voltage (200V AC with frequency of 1Hz), where the actuator was oscillating. For pressure ratio of 0.5, the flow rate was 0.62 sccm. © 2008 IOP Publishing Ltd.
Keywords: Ac voltage; Gas flow control; Micro nozzle; Micro valves; Piezoelectric coefficient; Piezoelectric polymers; Piezoelectric sheets; Powder blastings; Pressure ratio; Test sequence; Vertical movement; Volume flux; Electrodes; Piezoelectricity; Polymers; Pumps; Valves (mechanical); Piezoelectric actuators